Pengaruh Volume Koagulan Sari Buah Mengkudu (Morinda citrifolia L.) Terhadap Kadar Abu pada Koagulasi Lateks (Hevea brasiliensis) - ade putra tri prima; Jumar Jumar; Rabiatul Wahdah (Agroekotek View, 2021)
Rubber plants (Hevea brasilensis) include sap plants, because this group has plant tissue that contains a lot of latex and the sap flows out when the plant tissue is injured (Budiman, 2012). The obstacle most often encountered in the process of making rubber processed materials is the large number of farmers who use coagulation materials that are not recommended by the government, thus decreasing the quality of the rubber produced. Therefore, it is necessary to use alternative coagulants that do not degrade and damage the quality of rubber, such as noni juice. The purpose of this study was to determine whether the production of noni juice coagulant as a coagulant can affect the ash content of the latex and to determine the correct dose of noni juice coagulant in reducing the ash content of the latex. This study used a randomized block design (RBD) with a single factor and the factors studied were the addition of coagulant doses of noni juice with 7 treatments (K0: natural latex (control), K1: 25 ml, K2: 50 ml, K3: 75 ml. , K4: 100 ml, K5: 125 ml of noni juice coagulant material and K6: 25 ml of salvage 90 and added 1 l of latex per experimental unit). The results of this study indicate that the volume of the noni juice coagulant has a very significant effect on the contact time,  the gross weight of the bokar, and the ash content of the latex. The best dose of volume of noni juice coagulant to produce the lowest ash content of latex is the treatment of 75 ml of noni juice coagulant in 1 liter of liquid latex.